TANGGUNGJAWAB DIREKTORAT JENDERAL PAJAK ATAS KELALAIAN MENGAJUKAN TAGIHAN YANG MENGAKIBATKAN HILANGNYA HAK MENDAHULUI NEGERA DALAM KEPAILITAN - Suherman Nasution; Sunarmi Sunarmi; Mahmul Siregar; Faisal Akbar Nasution (USU LAW JOURNAL, 2018)
ABSTRACT   The position of the tax debt in the bankruptcy process should get the position ahead of other creditors, but this is different from the country where the tax debt in the bankruptcy process of PT. Badja Industry Garuda, Negara Cq. Medan Belawan KPP Pratama is placed as a concurrent creditor and loses its rights as a preferred creditor due to a tax debt bill filed by Medan Belawan Primary KPP that has exceeded 5 (five) years (expired) in accordance with Article 21 paragraph (4) and Article 22 of the KUP Law. Errors or omissions, both direct and indirect, carried out by Medan Belawan Primary KPP which cause harm to the state, in the concept of public law, the legal responsibility is related to the use of authority, which then gave rise to the principle of no authority without accountability. There are times when government organs are held accountable as officials, and sometimes as individuals.   Keywords: Responsibility, Negligence, Priority Rights